Weeping Toughs and Pretty Militants: Living Islam and Negotiating Gender in a Muslim Militia (Banser) - Ronald Lukens-Bull (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This paper explores the intersection of gender, religion, and militarism within Banser, the paramilitary wing of GP Ansor, affiliated with Nahdlatul Ulama—the world’s largest Muslim organization. Drawing on extensive ethnographic fieldwork, it examines how masculinity and femininity are negotiated in this male-dominated but increasingly gender-diverse organization. Through a ritual analysis of training camps and ceremonies, the paper unpacks emotional expression, moral formation, and the performance of Islamic piety in ways that challenge both normative gender roles and essentialist conceptions of Islam. Building on Talal Asad’s notion of Islam as a discursive tradition, the study develops a “linguistic model” to conceptualize Islamic variation as analogous to dialects—local articulations of a shared religious grammar. This model allows for an analysis of Javanese Islam as one such dialect, shaped by mysticism, hierarchy, and local understandings of gender. The paper also traces how militarized masculinity, inherited from Indonesia’s nationalist and New Order legacies, intersects with traditional and Islamic ideals, producing hybrid forms of moral militarism. Finally, it examines how female participation—through structures like Denwatser (Detasment Wanita Banser) and Garfa (Garuda Fatayat)—both challenges and is contained by existing gender hierarchies. Banser thus emerges as a site where lived Islam is actively negotiated through embodied practice, emotional intensity, and the disciplining of gendered selves. This study contributes to the anthropology of Islam by offering a grounded, theoretically rich account of how Islam is lived and contested in contemporary Indonesia.